Diagnosis and treatment for the early stage of cytomegalovirus infection during hematopoietic stem cell transplantation - Cui, Jiaqi; Zhao, Kui; Sun, Yanling; Wen, Ruijuan; Zhang, Xiangzhong; Li, Xudong; Long, Bing (Frontiers in Immunology, 2022)
Cytomegalovirus (CMV) infection remains a frequent complication after hematopoietic stem cell transplantation (HSCT) and causes significant morbidity and mortality in transplantation recipients. In this review, we highlight the role of major risk factors that are associated with the incidence of CMV infection. Advances in immunosurveillance may predict CMV infection, allowing early interventions to prevent severe infection. Furthermore, numerous therapeutic strategies against CMV infection after HSCT are summarized. A comprehensive understanding of the current situation of CMV treatment may provide a hint for clinical practice and even promote the development of novel strategies for precision medicine.